2015
DOI: 10.1007/s10681-015-1357-8
|View full text |Cite
|
Sign up to set email alerts
|

Marker assisted selection of Ty-2 and Ty-3 carrying tomato lines and their implications in breeding tomato leaf curl disease resistant hybrids

Abstract: Tomato leaf curl virus disease caused by whitefly-transmitted begomoviruses is a serious tomato production constraint in tropical and subtropical regions of the world. Use of genetic resistance for diseases caused by begomoviruses is an important component of sustainable disease management approaches. To date, six introgressions (Ty genes) derived from different tomato wild species that confer resistance to tomato leaf curl disease have been identified. Among these, dominant Ty-2 and partially dominant Ty-3 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…These findings suggest that instead of classical R gene-mediated hyper-sensitive response (HR), these Ty loci seem to adopt a different mechanism of strengthen host defense response. Prasanna et al [ 34 , 94 ] have shown that the combination of Ty-2 and Ty-3 genes enhanced the resistance level of tomato lines against ToLCNDV and betasatellite.…”
Section: Control Strategies To Reduce Disease Damagementioning
confidence: 99%
“…These findings suggest that instead of classical R gene-mediated hyper-sensitive response (HR), these Ty loci seem to adopt a different mechanism of strengthen host defense response. Prasanna et al [ 34 , 94 ] have shown that the combination of Ty-2 and Ty-3 genes enhanced the resistance level of tomato lines against ToLCNDV and betasatellite.…”
Section: Control Strategies To Reduce Disease Damagementioning
confidence: 99%
“…The tomato wild relatives that have been used include Solanum chilense (Zamir et al., ), Solanum habrochaites (Prasanna, Kashyap, et al. ; Prasanna, Sinha, et al. ), Solanum peruvianum (Lanfermeijer, Warmink, & Hille, ; Seah, Yaghoobi, Rossi, Gleason, & Williamson, ) , Solanum pennellii (Parniske et al., ), and Solanum pimpinellifolium (Chunwongse, Chunwongse, Black, & Hanson, ).…”
Section: Cwrs In Crop Improvementmentioning
confidence: 99%
“…In a recent study, tomato cultivars carrying a single wild‐derived TYLCY‐resistant gene, Ty‐2 or Ty‐3, or their pyramided lines, had greater yields in the presence of the pathogen TYLCY than cultivars lacking these genes (Prasanna, Kashyap, et al. ). The yield increases in these cases mostly are attributable to the enhanced resistance/tolerance to biotic or abiotic stresses generated by introducing the resistant/tolerant alleles from their wild relatives.…”
Section: Cwrs In Crop Improvementmentioning
confidence: 99%
“…For the first time in Indian long day onion population, DNA marker for male sterility and hybrid development has developed and identified with the help of which we can exploit the identified marker in future for hybrid development as well as transfer of male sterility to other onion lines or genotypes through marker assisted selections (Saini et al, 2015). Marker assisted selection has been employed in tomato for the introgression of Ty2 and Ty3 genes to develop tomato leaf curl resistant hybrid (Prasanna et al, 2015).…”
Section: Molecular Assisted Breeding To Fasten the Vegetable Improvemmentioning
confidence: 99%